Propagação vegetativa da pimenteira-do-reino : avaliação de cultivares, níveis de AIB e substratos - Secundino, Welington (2012)
Vegetative propagation by cuttings has largely contributed to the multiplication of several commercial species, among them the black pepper. Success in rooting is determined by a complex interaction between environmental and endogenous factors. The objective of this work is to investigate the course of cultivars of black pepper to indole-3-butyric acid (IBA) and different substrates. The experiments were conducted in a greenhouse equipped with irrigation system, type intermittent mist, located in the Centro Universitário Norte do Espírito Santo (CEUNES) of the Universidade Federal do Espírito Santo (UFES) in São Mateus, ES. In the first experiment, we investigated the rhizogenic course of black pepper cultivars by different concentrations of IBA. We used a randomized block design, with plots arranged in a factorial 3x5: three cultivars (Bragantina Iaçará and Guajarina) x five IBA concentrations (0, 1500, 3000, 4500 and 6000 mg kg-1 ), with four 16 replicates of each pile. It is recommended for cv. Bragantina immersion of only the basal and cvs. Iaçará Guajarina and total immersion of the cuttings in IBA, and the concentration recommended for cultivars is 4000 mg kg-1 . In the second experiment, xi we analyzed the rooting of cultivars of black pepper on different substrates. The experimental design was completely randomized in a 3x4 factorial design: three cultivars (Bragantina Iaçará and Guajarina) x four substrates (soil + organic compound - 18%, Vermiculite, semi-carbonized rice husk and Bioplant® ), with four 16 replicates of each pile. There are differences among cultivars of black pepper and the characteristics related to the root system. The vermiculite was the best and semicarbonized rice husk is not recommended for rooting cuttings of cvs. Bragantina Iaçará and Guajarina.